055 Novel sleep-dependent spatial memory and navigation task using Minecraft. (3rd May 2021) - Simon, Katharine; Clemenson, Gregory; Clayton, Brandon; Zhang, Jing; Alzueta, Elisabet; Dulai, Teji; Baker, Fiona; Mednick, Sara
Abstract: Introduction: Spatial navigation and memory are hippocampally-dependent and decrease with age, yet, ecologically-valid methods remain elusive. We developed an engaging and inherently flexible spatial navigation/memory task using the Minecraft platform to test sleep-dependent memory. We validated baseline performance and learning rates across two separate Minecraft environments. Methods: Using a within-subjects design, twenty-two subjects experienced two conditions (wake/sleep) and two Minecraft environments, counterbalanced across subjects. At encoding, subjects learned the locations of 12 objects. Memory for object location accuracy and navigation route (distance between start and target; vector: angle of direction towards target location from start) was tested immediately and following 12-hours of wake or sleep. Post-hoc analyses were conducted using a median split on subjects' Immediate test performance. Results: There were no significant differences across conditions for the Immediate test performance (t(22) = .567, p = .576) across the two environments. Delayed test showed greater improvement in accuracy after sleep compared to wake (t(18) = 2.795, p=.012), no differences in distance or vector. Median split by Immediate test performance revealed that initially lower performance showed the greatest improvement after delay in the sleep group (t(18) = 2.818, p =.011), but not the wake group (t(18) = -1.051, p =.308). Additionally, these same subjects' vector direction was initially worse at Immediate Test (t(18) = -2.9, p = .01), and improved with sleep, becoming equivalent to the better performers at Delay test (t(18) = -.336, p = .74). Conclusion: We demonstrate a novel spatial navigation/memory tasks using Minecraft that shows sleep-dependent learning across two distinct environments. We showed enhancement of spatial location accuracy after a night of sleep compared to wake. We further demonstrate that with sleep, those with worse initial performance show the greatest memory and navigation improvement, consistent with other findings that sleep supports enhancement of weaker memories and extended to the spatial-domain. This novel platform can be used to evaluate spatial memory across the lifespan and within special clinical populations. Support (if any): NIH R01 AG061355